Anti-inflammatory effect of simvastatin by impeding TNF-α and interleukin-1ß pathways: antiangiogenic activity of simvastatin and simvastatin-loaded silver nanoparticles - Manal Buabeid; El-Shaimaa A. Arafa; Hafiza Sidra Yaseen; Muhammad Ihtisham Umar; Ghulam Murtaza (Artificial Cells, Nanomedicine, and Biotechnology, 2022)
Purpose The present study was carried out to evaluate anti-inflammatory and antiangiogenic attributes of simvastatin and its nanofilms containing silver nanoparticles.Methods Silver nanoparticles and simvastatin-loaded nanocomposite (SNSN) films were formulated by using polymeric solution (pectin + sericin) through casting solution method. Different in vitro and in vivo anti-inflammatory assays were performed. In addition, chick chorioallantoic membrane assay (CAM) was also employed for angiogenesis activity.Results FTIR spectra of the film depicted the presence of intact simvastatin. Differential scanning calorimetry exhibited no endothermic expression in F9 film thermogram. The simvastatin release from all films exhibited a burst effect. Cotton-pellet induced granuloma model study showed that high dose of simvastatin and indomethacin produced comparable (p < 0.05) anti-inflammatory effect. Noteworthy, RT-PCR showed dose-dependent, anti-oedematous effect of simvastatin through downregulation of serum TNF-α and interleukin-1ß levels. While results of CAM assay exhibited remarkable anti-angiogenic potential of SNSN films showing dissolved blood vessels network macroscopically.Conclusion To reiterate, simvastatin and its SNSN films can add significant contribution to the field of biomedicines due to their promising anti-inflammatory and antiangiogenic properties, however, clinical studies are required to validate their commercial use.